Kinematic analysis of volleyball jump topspin and float serve - Huang, C. F.; Hu, L.-H. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The purpose of this study is to describe the kinematic characteristics of the volleyball jump topspin and float serve. Thirteen international players performed jump topspin serves and another three players executed jump float serves participated in this study. Two JVC 9800 cameras (120Hz) recorded the players performed jump serves. The results show the jump topspin serve has greater values than the jump float serve on ball velocity, COM velocities at takeoff, jump height, spike height, takeoff to line distance, and horizontal COM displacement. In addition, the mean 1.0cm and 0.7cm of COM spike difference for jump topspin and float serve indicates that elite volleyball players have good timing control during serve action. It is suggested that results from this study can provide useful information for coaches to train volleyball jump topspin and float serve.